KELAYAKAN BOOKLETMATERI KEANEKARAGAMAN HAYATI DARI BUAH KAPANGKELADI RAWA DAN MELINJO HUTAN - Maemunah, Maemunah; Daningsih, Entin; Titin, Titin (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstractÂ This study aimed to determine the feasibility of booklet media on biodiversity material of class X in high school from morphology and nutrient content as well as fiber fruit of kapang (Knema conferta), keladi rawa (Cyrtosperma merkusii) and melinjo hutan (Gnetum loufounse) which found in the Sibohe Pajintan east Singkawang forest, Singkawang City, West Kalimantan. Some information from the results of morphological analysis and nutritient content was implemented in booklet shaped learning media. This research was descriptive method using purposive sampling technique with two stages, namely instrument validation and media validation. Instrument validation was carried out by three validators, two biology education lecturers and one high school biology teacher who taught class X. The media validation was conducted by five validators consisting of two biology education lecturers from FKIP Tanjungpura University and three high school biology teachers. Data were analyzed by Lawshe method with CVR and CVI formulas. Based on the results of the instrument validation using the questioner sheet with five aspects consisting of 14 criteria showed that it was feasible to be used and repaired, while for media validation obtained a CVI value of 0.99 which corresponded to Lawshe's minimum CVI value for 5 validators, namely 0.99 so that the booklet media declared valid and feasible to be used as a biodiversity material learning media for class X high school.Keywords: Booklet, Biodiversity, Kapang, Keladi Rawa, Melinjo hutan